PENGARUH PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA KIMIA MATERI ASAM BASA TERHADAP HASIL BELAJAR PESERTA DIDIK FASE F SMA/MA - Ramadhani, Nurul Fitri; Iswendi, Iswendi (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study is based on the availability of a chemical snakes and ladders game about acid-base material in the form of exercises that have been tested for validity, practicality, and effectiveness, but have not yet been tested for their effect on students' cognitive learning outcomes. The purpose of this study is to analyze the effect of using the chemical snakes and ladders game on acid-base material on the cognitive learning outcomes of grade XI Fase F students at SMAN 1 Banuhampu. The type of research used is Quasi-Experimental Research through a Posttest Only Control Group Design. The research population includes all grade XI Chemistry students at SMAN 1 Banuhampu. The sample was selected using Total Sampling technique, so that the 11th grade Chemistry 1 class became the experimental group and the 11th grade Chemistry 2 class became the control group. The research instrument was a learning outcome test (posttest) with 20 multiple-choice questions. The average learning outcomes of students in the experimental group were 82.71, while those in the control group were 78. The data were analyzed using a t-test at a significance level of ? = 0.05. The results showed that the calculated t-value was 1.80 and the table t-value was 1.66, meaning that the calculated t-value exceeded the table t-value. Therefore, it can be concluded that the use of the chemistry snakes and ladders game had a significant effect on the cognitive learning outcomes of students in the 11th grade Fase F class at SMAN 1 Banuhampu. ABSTRAKPenelitian ini didasarkan pada ketersediaan permainan ular tangga kimia tentang materi asam-basa berbentuk latihan yang sudah dilakukan uji validitas, praktisitas, serta efektivitas, namun belum diuji pengaruhnya terhadap hasil belajar kognitif peserta didik. Tujuan penelitian ini adalah menganalisis pengaruh penggunaan media permainan ular tangga kimia pada materi asam-basa terhadap hasil belajar kognitif peserta didik kelas XI Fase F SMAN 1 Banuhampu. Jenis penelitian yang digunakan yaitu Quasi-Experimental Research melalui rancangan Posttest Only Control Group Design. Populasi penelitian meliputi seluruh peserta didik kelas XI Kimia di SMAN 1 Banuhampu. Sampel dipilih menggunakan teknik Sampling Total, sehingga kelas XI Kimia 1 menjadi kelompok eksperimen serta kelas XI Kimia 2 menjadi kelompok kontrol. Instrumen penelitian ini berupa tes hasil belajar (posttest) dengan 20 soal pilihan ganda. Rata-rata hasil belajar peserta didik di kelompok eksperimen yaitu 82,71, sedangkan di kelompok kontrol 78. Data dianalisis mempergunakan uji t pada tingkat signifikansi ? = 0,05. Hasil ini memperlihatkan bahwasanya nilai thitung 1,80 serta nilai ttabel 1,66, sehingga nilai thitung melebihi ttabel. Dengan demikian, dapat disimpulkan bahwasanya penggunaan permainan ular tangga kimia berpengaruh secara signifikan terhadap hasil belajar kognitif peserta didik kelas XI Fase F SMAN 1 Banuhampu.